Ephemeral drawing. Street art between conservation and impermanence - Giovanni Caffio (Agathón)
The debate on the relationship between street art and contemporary culture is still alive and offers always new spaces for discussion. Starting from the specific discipline of drawing, this paper deals with the need to set up the documentation path (survey) of an artistic-urban practice that is intrinsically ephemeral and then, often, becomes enduring, thus entering the broader system of cultural heritage. The purpose of this research is to hypothesize a process of documentation and representation that, considering the complexity of internal and external references to the artwork, includes a variety of methods and restitution techniques necessarily integrated. Moreover, in addition to the physical aspect, temporal dimension should also be considered by documenting the variations that the drawing and its wall structure undergo over time to grasp the way the public has reacted to.